2015
DOI: 10.1055/s-0034-1391844
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of endoscopic submucosal dissection for superficial esophageal neoplasms: a multicenter retrospective cohort study

Abstract: Esophageal ESD has become feasible with acceptable complication risks and favorable long term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
147
7
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 188 publications
(165 citation statements)
references
References 28 publications
(42 reference statements)
9
147
7
2
Order By: Relevance
“…Conversely, one LSBE case developed several metachronous adenocarcinomas, which poses a problem regarding metachronous cancer from residual Barrett's epithelium. The cumulative 3-year metachronous cancer rate of LSBE (8.3%) was similar to that reported for esophageal SCC (9.9%) [25]. In view of the effective long-term outcome of ESD for esophageal SCC, metachronous cancers from LSBE in Japan may be controlled by repeat local resection using ESD.…”
Section: Discussionsupporting
confidence: 78%
“…Conversely, one LSBE case developed several metachronous adenocarcinomas, which poses a problem regarding metachronous cancer from residual Barrett's epithelium. The cumulative 3-year metachronous cancer rate of LSBE (8.3%) was similar to that reported for esophageal SCC (9.9%) [25]. In view of the effective long-term outcome of ESD for esophageal SCC, metachronous cancers from LSBE in Japan may be controlled by repeat local resection using ESD.…”
Section: Discussionsupporting
confidence: 78%
“…ESD is the first-line therapeutic option for superficial gastrointestinal tract tumors[1,6,18-20]. The devices used in ESD are important for performing the procedure safely.…”
Section: Discussionmentioning
confidence: 99%
“…First, the DPC database lacks some information about clinicopathological features in esophageal ESD, such as the location, size, configuration, circumferential involvement, depth of lesions, submucosal invasion, submucosal adhesion, and the presence of scar tissue. However, a recent study conducted in Japan, which included 368 esophageal ESDs among 11 hospitals, suggested that there were no differences in lesion factors between the highvolume centers and low-volume centers [21]. The database also lacks data regarding experience of the endoscopists who perform ESD procedures, number of endoscopists working at the hospital, types of endoscopy knives used, use of carbon dioxide insufflation vs. room air insufflation, and duration of the procedure.…”
Section: Discussionmentioning
confidence: 99%